Development of the anxiety scale for children with autism spectrum disorder (ASC‐ASD). Issue 11 (17th February 2016) - Rodgers, Jacqui; Wigham, Sarah; McConachie, Helen; Freeston, Mark; Honey, Emma; Parr, Jeremy R.
Abstract : Many children with autism spectrum disorder (ASD) experience high levels of anxiety. A widely used measure for typically developing children is the Revised Child Anxiety and Depression Scale (RCADS). However, such anxiety measures may require adaptation to accommodate characteristics of those with ASD. An adapted version of the RCADS was created based on empirical evidence of anxiety phenomenology in ASD, which included additional items related to sensory anxiety, intolerance of uncertainty, and phobias. Content validity was refined during focus groups with parents. Polychoric factor analysis was undertaken on data from 170 children with ASD, aged 8‐16, and their parents. This process resulted in the creation of a new 24 item scale (self and parent report) each with four subscales: Performance Anxiety, Uncertainty, Anxious Arousal, and Separation Anxiety, with evidence of good reliability and validity. The freely available Anxiety Scale for Children ‐ ASD, Parent and Child versions (ASC‐ASD) has promising psychometric properties including good internal consistency, validity, and 1 month test–retest reliability. Autism Res 2016, 9: 1205–1215 . © 2016 International Society for Autism Research, Wiley Periodicals, Inc.